Endogenous Vertical Restraints in International Trade - Horst Raff; Nicolas Schmitt (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper examines interbrand competition between a domestic and a foreign manufacturer who market their products through intermediaries. The contracts manufacturers offer these intermediaries are endogenous. In equilibrium contracts may specify exclusive territories (ET), depending on the degree of substitutability between products and the level and degree of transparency of trade barriers. Trade liberalization, through lower or more transparent barriers, may lead manufacturers to use ET, thereby substituting private anti-competitive arrangements for government-imposed barriers. This substitution may decrease competition and welfare, and thus create a role for competition policy in a freer trade environment.
Keywords: 330